Enhancing physical-mechanical properties of coarse slag aggregate via selective crushing for asphalt concrete - Vyacheslav Kunaev; Gulzhainat Akhmetova; Bakhyt Zhautikov; Alibek Batyrbek; Ilgar Tavshanov; Dmitriy Charnyi; Saltanat Kydyrbayeva; Saule Kamarova; Mohamad Syazli Fathi; Bakhtiyar Suleyev (Results in Engineering)
Air-cooled blast furnace slag is a solid metallurgical waste that can serve as coarse aggregate in asphalt concrete mixtures. However, its application is limited by considerable variability in key physical and mechanical properties, including compressive strength (ranging from 2 to 30 MPa), water absorption (1–30 %), aggregate crushing value (18–37 %), and frost resistance. This highlights the need for preliminary enrichment of the material through selective crushing, during which low-quality grains are destroyed and strength grains retain their integrity and can be used in asphalt concrete production. This paper presents a study on how selective crushing duration affects the physical and mechanical properties of air-cooled blast furnace slag. Selective crushing in a ball mill for 30–40 min, using a grinding medium consisting of 50 % balls and 50 % cylpebs, effectively destroys low-quality (high-porosity and low-strength) grains while preserving high-quality (low-porosity and high-strength) grains. As a result of low-quality grain removal, the bulk density of air-cooled blast furnace slag increased from 1169 kg/m³ to 1396 kg/m³. Water absorption decreased from 4.96 % to 2.38 %, aggregate crushing value decreased from 30.98 % to 18.4 %, mass loss after sulfate soundness testing decreased from 5.48 % to 1.23 %, and surface pore content decreased from 45.06 % to 15.68 %. Thus, pre-enrichment by selective crushing enhances the mechanical properties of air-cooled blast furnace slag and expands its potential for effective use in asphalt concrete mixtures.